Ellagic acid alleviates pulmonary inflammation and oxidative stress in mouse model of diisononyl phthalate-induced asthma - Olajide, Abosede Temitope; Olayinka , Ebenezer Tunde; Ore, Ayokanmi; Kehinde, Samuel Abiodun; Okoye, Cynthia Chisom (Life Sciences, Medicine and Biomedicine, 2023)
Polyvinyl chloride is plasticized using diisononyl phthalate (DiNP), and exposure to phthalates has been linked to the emergence of asthma and allergies. The adjuvant impact of DiNP exposure results in allergic airway inflammation. In the current study, we looked into how ellagic acid (ELA) impacted asthma brought on by DiNP. Male BALB/c mice (n=40, 20-30 g) were divided into 4 groups of 10 mice each, and the following treatments were given to each group: group 1 (control) received saline orally for 30 days; group 2 (ELA) received 10 mg/kg of ELA (oral) for 30 days; group 3 (DiNP & ELA) received 10 mg/kg of ELA (oral) for 7 days prior to DiNP (50mg/kg) exposure (intraperitoneal and intranasal); group 4 (DiNP) received 50 mg/kg DiNP. After the last administration, mice were sacrificed, lungs were removed and their bronchoalveolar lavage fluid was collected which was used for biochemical and histopathological analysis. The mice given DiNP had changes in their histoarchitecture, inflammatory cells, antioxidant status, and inflammation markers. Malondialdehyde (MDA) and inflammatory biomarkers (NO, MPO) were considerably higher (p< 0.05) in the lungs of DiNP-treated mice than in the control group. In the lungs, DiNP reduced the concentration of non-enzymatic antioxidants (GSH and AA), and the activity of enzymatic antioxidants (SOD, CAT, and GST). DiNP also altered inflammatory cells (eosinophils, neutrophils, lymphocytes, monocytes, leucocytes) in the BALF. ELA administration ameliorated these changes. Histopathological analysis revealed airway inflammation characterized by inflammatory cell infiltration, oedema, hemorrhage, and constricted alveoli space. Additionally, the mice co-treated with ELA and DiNP experienced mild inflammation of the alveoli and interstitial spaces as well as mild thickening of the alveolar septae. ELA offered a protective effect against DiNP-induced allergic asthma in mice.